2017
DOI: 10.17650/1726-9784-2017-16-1-61-69
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumor Effect of Cpda Enantiomers in Vitro in the Model of Acute Lymphoblastic Leukemia

Abstract: Introduction. Glucocorticoids are the important component of combined chemotherapy of blood cancer. Therapeutic effects of glucocorticoids is realized via activation of glucocorticoid receptor transrepression, the development of side effects is associated with transactivation. We demonstrated earlier that compound belonging the class of selective glucocorticoid receptor agonists, CpdA, selectively induced transrepression in blood cancer cells. CpdA represents a mixture of two enantiomers, which can differ in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Of note, CpdA enantiomers slightly differ in their biological effects from a racemic mixture. In our previous studies, we synthesized CpdA enantiomers, and in our in vitro studies S-CpdA was revealed to exert stronger proapoptotic effects on leukemia cells as compared to R-CpdA [41]. The p-synephrine isomer is widely used as a dietary supplement for weight loss since it promotes fat oxidation [1,6].…”
Section: Source Chemical and Pharmacological Features Of Synephrinementioning
confidence: 99%
See 1 more Smart Citation
“…Of note, CpdA enantiomers slightly differ in their biological effects from a racemic mixture. In our previous studies, we synthesized CpdA enantiomers, and in our in vitro studies S-CpdA was revealed to exert stronger proapoptotic effects on leukemia cells as compared to R-CpdA [41]. The p-synephrine isomer is widely used as a dietary supplement for weight loss since it promotes fat oxidation [1,6].…”
Section: Source Chemical and Pharmacological Features Of Synephrinementioning
confidence: 99%
“…CpdA, a well-characterized SEGRA, is a synthetic analog of a natural compound found in Salsola tuberculatiformis Botschantzev and exerts GR-dependent anti-inflammatory and anti-cancer effects [16,41,62,63]. CpdA appears to be a promising alternative to GCs with fewer side effects [18,41,51,62,[64][65][66].…”
Section: Chemical and Pharmacological Features Of Cpda And Its Target...mentioning
confidence: 99%